Pengaruh Penggunaan Artificial Intelligence (AI) dan Literasi Digital terhadap Kemampuan Akademik Mahasiswa Jurusan Ekonomi Stambuk 2023 Fakultas Ekonomi dan Bisnis Universitas Negeri Medan - Mutiara Dwi Rizqina; Muhammad Fitri Rahmadana (WISE Pendidikan Indonesia, 2026)
The rapid integration of artificial intelligence (AI) into higher education has expanded students' access to academic support, yet its educational value may depend on students' capacity to navigate and evaluate digital information critically. This study examined the effects of AI use and digital literacy on the academic ability of Economics Department students from the 2023 cohort at the Faculty of Economics and Business, Universitas Negeri Medan. Using a quantitative ex post facto design, data were collected from 158 students selected from a population of 261 through questionnaire-based measures and analyzed using instrument testing, classical assumption tests, multiple linear regression, partial t-tests, an F-test, and the coefficient of determination. AI use had a positive and statistically significant effect on academic ability (t = 2.798, p = .006), while digital literacy showed a stronger positive and significant effect (t = 5.840, p < .001). Jointly, both predictors significantly explained academic ability (F = 47.630, p < .001), with R² = .381, indicating that 38.1% of the variance was accounted for by the model. These findings demonstrate that AI is most educationally meaningful when accompanied by students' capacity to access, evaluate, verify, and use digital information responsibly. The study implies that universities should integrate AI-use guidance with systematic digital-literacy development so that AI functions as a cognitive support tool rather than a substitute for independent academic reasoning.